Manajemen nyeri non farmakologis dalam pengurangan nyeri pada bayi berat badan lahir rendah (BBLR): A systematic review - Setyaningsih, Wahyu; Ramawati, Dian (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Pain management for LBW undergoing treatment in hospital is crucial. LBW often receive invasive procedures, so both pharmacological and non-pharmacological pain management is needed. Therefore, non-pharmacological pain management is needed which not only reduces pain but can stimulate the baby's growth and development. Purpose: To analyze the success of pain management using non-pharmacological methods during intravenous insertion procedures, blood sampling, and to assess the effect on pain reduction by measuring using the Premature Infant Pain Profile (PIPP) score. Method: Review of research articles obtained from the ProQuest, Science Direct, PubMed, Oxford, and SAGE Journal databases. The inclusion criteria for this study were articles with a randomized control trial (RCT) research design published between 2017-2023. The keywords used in the PICO search process were